Extracorporeal shock wave therapy for digital ulcers associated with systemic sclerosis. Issue 2 (May 2016) - Saito, Shinichiro; Ishii, Tomonori; Ito, Kenta; Shimokawa, Hiroaki
Patients with systemic sclerosis (SSc) often have Raynaud's phenomenon and digital skin ulcers. These ulcers are painful, and can sometimes cause major functional limitation. Skin ulcers are not associated with autoimmune factors or abnormal coagulation; hence, conventional immunosuppressive therapies, vasodilators, and anticoagulants are often ineffective. Sometimes, patients are forced to continue expensive medication without appreciable change. Therefore, the loss in time and expense for both patients and society is not negligible, and appropriate management is needed. Low-energy extracorporeal shock wave therapy (ESWT) enhances vascular endothelial growth factor production by endothelial cells and angiogenesis in vivo. Clinical application of low-energy ESWT for severe ischemic heart disease or refractory skin ulcers has been effective in treating ischemic symptoms. This treatment does not require anesthesia or any invasive procedure, and can be repeated without harmful side effects. We conducted a pilot study involving a small group of subjects to collect basic data on the efficacy and safety of ESWT for digital ulcers associated with SSc and to compare the effect of ESWT with that of conventional therapies. The results of our study suggest that ESWT has the potential to be a novel and efficacious treatment for digital ulcers associated with SSc, and can be added to pharmacological therapy.